Benchmarking the quality of multiplexed qubit readout beyond assignment fidelity - Di Giovanni, Andras; Aasen, Adrian Skasberg; Lisenfeld, Jürgen; Gärttner, Martin; Rotzinger, Hannes; Ustinov, Alexey V. (Physical review applied, 2025)
The accurate measurement of quantum two-level objects (qubits) is crucial for developing quantum computers. Over the last decade, the measure of choice for benchmarking readout routines for superconducting qubits has been assignment fidelity; however, this method only focuses on the preparation of computational basis states and therefore does not provide a complete characterization of the readout. Here, we expand the focus to the use of detector tomography to fully characterize multiqubit readout of superconducting transmon qubits. The impact of different readout parameters on the rate of information extraction is studied using quantum-state reconstruction infidelity as a proxy. The results are then compared with assignment fidelities, showing good agreement for separable two-qubit states. We therefore propose the rate of infidelity convergence as a validation tool for assignment fidelity and a more comprehensive benchmark for single- and multiqubit readout optimization. To make the best use of experimental resources, we investigate the most efficient distribution of a limited shot budget between detector tomography and state reconstruction within the context of single- and two-qubit experiments. To address the growing interest in three-qubit gates and test the scalability of the validation tool, we perform three-qubit quantum-state tomography that goes beyond conventional readout-error-mitigation methods and find a factor-of-30 reduction in quantum infidelity. Our results demonstrate that qubit readout correlations are not induced by a significantly reduced state distinguishability. Consequently, correlation coefficients can serve as a valuable tool in qubit readout optimization.
Gesehen am 24.02.2026